DPB162-AE, an inhibitor of store-operated Ca2+ entry, can deplete the endoplasmic reticulum Ca2+ store. (March 2017) - Bittremieux, Mart; Gerasimenko, Julia V.; Schuermans, Marleen; Luyten, Tomas; Stapleton, Eloise; Alzayady, Kamil J.; De Smedt, Humbert; Yule, David I.; Mikoshiba, Katsuhiko; Vangheluwe, Peter; Gerasimenko, Oleg V.; Parys, Jan B.; et al.
Graphical abstract: Highlights: The SOCE inhibitor DPB162-AE, a 2-APB analogue, depletes the ER Ca 2+ stores. DPB162-AE does not inhibit SERCA ATPase activity. DPB162-AE accelerates the ER Ca 2+ leak after thapsigargin treatment. DPB162-AE induces an ER Ca 2+ leak pathway, to which IP3 Rs partially contribute. Abstract: Store-operated Ca 2+ entry (SOCE), an important Ca 2+ signaling pathway in non-excitable cells, regulates a variety of cellular functions. To study its physiological role, pharmacological tools, like 2-aminoethyl diphenylborinate (2-APB), are used to impact SOCE. 2-APB is one of the best characterized SOCE inhibitors. However, 2-APB also activates SOCE at lower concentrations, while it inhibits inositol 1, 4, 5-trisphosphate receptors (IP3 Rs), sarco/endoplasmic reticulum Ca 2+ -ATPases (SERCAs) and other ion channels, like TRP channels. Because of this, 2-APB analogues that inhibit SOCE more potently and more selectively compared to 2-APB have been developed. The recently developed DPB162-AE is such a structural diphenylborinate isomer of 2-APB that selectively inhibits SOCE currents by blocking the functional coupling between STIM1 and Orai1. However, we observed an adverse effect of DPB162-AE on the ER Ca 2+ -store content at concentrations required for complete SOCE inhibition. DPB162-AE increased the cytosolic Ca 2+ levels by reducing the ER Ca 2+ store in cell lines as well as in primary cells. DPB162-AE did not affect SERCA activity, but provoked a Ca 2+ leak from the ER, even after application of the SERCA inhibitor thapsigargin. IP3 Rs partly contributed to the DPB162-AE-induced Ca 2+ leak, since pharmacologically and genetically inhibiting IP3 R function reduced, but not completely blocked, the effects of DPB162-AE on the ER store content. Our results indicate that, in some conditions, the SOCE inhibitor DPB162-AE can reduce the ER Ca 2+ -store content by inducing a Ca 2+ -leak pathway at concentrations needed for adequate SOCE inhibition.